Pengembangan Local Instructional Theory Topik Penjumlahan dan Pengurangan Bilangan Berbasis Pendekatan Realistic Mathematics Education Untuk Kelas II Sekolah Dasar - Mardha Tillah; Ahmad Fauzan; Melva Zainil; Ulfia Rahmi (Universitas Negeri Padang, 2025)
This study aims to develop a valid, practical, and effective instructional design to improve students’ mathematical problem-solving abilities on the topic of addition and subtraction. The study was motivated by the lack of structured learning trajectories and the low level of students’ problem-solving skills in elementary mathematics. This research employed a Design research method by combining the Plomp development model and the Gravemeijer and Cobb model, consisting of three phases: preliminary research, development or prototyping, and assessment. The effectiveness of the developed design was examined through a field test using a one-group evaluation design involving second-grade students at SDN 26 Bukit Putus Dalam and SDN 20 Muara Jambu. Data were collected through observation, questionnaires, documentation, and tests, and analyzed using qualitative and quantitative techniques. The results indicate that the developed instructional design is highly valid (96.25%), very practical (93.22%), and effective in improving students’ mathematical problem-solving abilities, as shown by the increase in students’ performance during the implementation phase